Application of environmental isotopes to identify recharge source, age, and renewability of phreatic water in Yinchuan Basin. Issue 16 (23rd May 2019) - Zhong, Chenghao; Yang, Qingchun; Ma, Hongyun; Bian, Jianmin; Zhang, Sihong; Lu, Xiaoguang
Abstract: The accurate understanding of groundwater circulation pattern and its renewable capacity is vital for groundwater resource assessment and the rational exploitation and utilization of groundwater. Estimation of groundwater recharge is difficult in arid or semiarid area due to the low amount and variability of recharge. A combination of isotope investigation with hybrid model allows a direct calculation of renewability of the aquifer. In this paper, the phreatic water circulation pattern and its renewable capacity of phreatic water in Yinchuan Basin, a semiarid area located at the northwest China, are investigated by the application of environmental isotope method, which mainly focusses on the isotope characteristics of different water bodies, phreatic water isotope age, phreatic water circulation pattern, and phreatic water renewal rate. The results demonstrate that the two dominant recharge sources of groundwater in Yinchuan Basin, local atmospheric precipitation and Yellow River, account for 13% and 87%, respectively. The average residence time of phreatic water in Yinchuan Basin is about 48 years, and the average renewal rate is 3.38%/a. The results indicate that the phreatic water has a strong renewable capacity and the regeneration rate distribution is consistent with that indicated by isotope age.